Exploring the Role of Search Experience and Self-Efficacy in Cognitive Self-Esteem: A Latent Growth Modelling Approach - Mahir Akgün; Sacip Toker (SAGE Open)
In this study, we seek to contribute to a broader understanding of the processes and contexts that lead to inflated judgments of cognitive ability in human-computer partnerships. We conducted a within-subject experiment design study with 164 college students in order to explore the impact of the search experience on cognitive self-esteem (CSE). Our preliminary findings revealed that search experience is an important factor that influences individuals’ perception of their abilities to answer questions. This influence was observed regardless of whether they have access to search tools or not. However, search experience does not explain the significant change in CSE that we found between “access” and “no access” (to search tools) conditions.